Precision Medicine in Pharmacy Practice: Advancements and Implications - H, Athul. (Indian Journal of Pharmacy Practice)
Precision medicine, which is often referred to as personalised medicine, is a cutting-edge approach to healthcare that aims to customise medical treatments for individual patients according to their lifestyle, genetic composition, and environmental circumstances. Precision medicine, which emphasises pharmacogenomics, individualised medication regimens, and the use of biomarkers to improve patient care, has completely changed the way pharmacists approach drug therapy in pharmacy practice. The function of precision medicine in pharmacy practice is covered in this review article, which also highlights significant developments, difficulties, and potential paths forward.
Keywords: Precision medicine; Pharmacy practice; Pharmacogenomics; Personalised drug therapies; Biomarkers; Patient care; Genetic testing; Treatment optimization